2005
DOI: 10.1074/jbc.m502333200
|View full text |Cite
|
Sign up to set email alerts
|

Ras-ERK MAPK Cascade Regulates GATA3 Stability and Th2 Differentiation through Ubiquitin-Proteasome Pathway

Abstract: Differentiation of naive CD4 T cells into Th2 cells requires protein expression of GATA3. Interleukin-4 induces STAT6 activation and subsequent GATA3 transcription. Little is known, however, on how T cell receptor-mediated signaling regulates GATA3 and Th2 cell differentiation. Here we demonstrated that T cell receptor-mediated activation of the Ras-ERK MAPK cascade stabilizes GATA3 protein in developing Th2 cells through the inhibition of the ubiquitin-proteasome pathway. Mdm2 was associated with GATA3 and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
124
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 65 publications
(65 reference statements)
8
124
1
Order By: Relevance
“…The hyperacetylation of histones associated with the Th2 cytokine gene locus is dependent on the expression of GATA3 (43,46). Activation of the ERK-MAPK cascade is required for GATA3-dependent histone H3 hyperacetylation of the Th2 cytokine gene locus (16). Consequently, we wished to examine the chromatin remodeling of the Th2 cytokine gene locus in CD4 ϩ T cells from aging mice.…”
Section: Chromatin Remodeling Of the Th2 Cytokine Gene Locus In Cd4 ϩmentioning
confidence: 99%
See 3 more Smart Citations
“…The hyperacetylation of histones associated with the Th2 cytokine gene locus is dependent on the expression of GATA3 (43,46). Activation of the ERK-MAPK cascade is required for GATA3-dependent histone H3 hyperacetylation of the Th2 cytokine gene locus (16). Consequently, we wished to examine the chromatin remodeling of the Th2 cytokine gene locus in CD4 ϩ T cells from aging mice.…”
Section: Chromatin Remodeling Of the Th2 Cytokine Gene Locus In Cd4 ϩmentioning
confidence: 99%
“…The methods for the generation of the virus supernatant and infection were described previously (16).…”
Section: Retroviral Vectors and Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the transcriptional regulation, the expression of GATA3 is also regulated by a posttranscriptional mechanism. We recently reported that the Ras-ERK MAPK cascade controls GATA3 stability through the ubiquitin/ proteasome-dependent pathway (21).…”
mentioning
confidence: 99%